2004
DOI: 10.1287/inte.1040.0073
|View full text |Cite
|
Sign up to set email alerts
|

Metrics for Managing Online Procurement Auctions

Abstract: Metrics can improve firms' ability to manage online procurement auctions. A key factor in business-to-business procurement auctions is supplier participation, which we modeled as a multistage process. We analyzed data collected from thousands of auctions conducted by a large multinational firm and found that different auction types lead to different participation and success dynamics. Typically, it is important to invite a sufficient number of suppliers and ensure that they accept the invitation and actually l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 28 publications
7
59
0
7
Order By: Relevance
“…This has resulted in growing interest, by both the marketplace and academics, in the use of partial price visibility formats. Using data from over 14,000 auctions, Millet et al (2004) found that revealing the lowest bid and bid rank to suppliers can yield greater price savings than less visible formats (i.e., low bid only or rank bid only). Jap (2007) shows that partial price visible formats (e.g., particularly the rank format over the low price format) are better at preserving the buyer-supplier relationship (e.g., minimizing opportunism suspicions, protecting overall satisfaction and future expectations) than full price visibility formats.…”
Section: Award Rulesmentioning
confidence: 99%
“…This has resulted in growing interest, by both the marketplace and academics, in the use of partial price visibility formats. Using data from over 14,000 auctions, Millet et al (2004) found that revealing the lowest bid and bid rank to suppliers can yield greater price savings than less visible formats (i.e., low bid only or rank bid only). Jap (2007) shows that partial price visible formats (e.g., particularly the rank format over the low price format) are better at preserving the buyer-supplier relationship (e.g., minimizing opportunism suspicions, protecting overall satisfaction and future expectations) than full price visibility formats.…”
Section: Award Rulesmentioning
confidence: 99%
“…Academic interest in online reverse auctions is also on the rise, with growing streams of research on the benefits and risks of online reverse auctions (Mabert and Skeels 2002;Smeltzer and Carr 2003) as well as the performance implications of auction design choice which are both economic (Carter et al 2004;Engelbrecht-Wiggans et al 2007;Millet et al 2004) and relational (Jap 2003(Jap , 2007.…”
Section: Interorganizational Relationships and Bidding Behavior In Inmentioning
confidence: 99%
“…More specifically, InterOrganizational Information Systems (IOS) have been presented as a key driver, enabling buying firms to enhance their negotiation power (Saeed et al, 2005). Among these systems, online reverse auctions (ORAs) have become a fixture and even a standard for business negotiation (Beall et al, 2003;Carter and Stevens, 2007;Millet et al, 2004;Tully, 2000). In effect, the technology has become extremely popular (Wilson, 2007) and strategic (Carbone, 2005) with buyers thanks to the huge savings it can theoretically procure for buying firms (Brunelli, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is subject to fierce debate as it is widely blamed for a pricing focus only Stec, 2004, 2005), dehumanizing business relationships (Charki and Josserand, 2008) and neglecting other differentiation sources such as suppliers' capabilities, qualities and innovation (Bartholomew, 2002;Stec, 2001, 2004;Handfield and Nichols, 2004;Jap, 2002). Suppliers are therefore very wary of the technology (Millet et al, 2004) and only a small number express a positive opinion of it (Caniëls et al 2009), with most considering it as intrinsically unethical business practice Stec, 2004, 2005). However, no in-depth study of actors' ethical judgments has appeared in the literature to date.…”
mentioning
confidence: 99%